Therapeutic application of mesenchymal stem cell-derived exosomes: A promising cell-free therapeutic strategy in regenerative medicine - Motavaf, M; Pakravan, K; Babashah, S; Malekvandfard, F; Masoumi, M; Sadeghizadeh, M (Cellular and Molecular Biology, 2016)
Mesenchymal stem cells have emerged as promising therapeutic candidates in regenerative medicine. The mechanisms underlying mesenchymal stem cells regenerative properties were initially attributed to their engraftment in injured tissues and their subsequent transdifferentiation to repair and replace damaged cells. However, studies in animal models and patients indicated that the low number of transplanted mesenchymal stem cells localize to the target tissue and transdifferentiate to appropriate cell lineage. Instead the regenerative potential of mesenchymal stem cells has been found - at least in part - to be mediated via their paracrine actions. Recently, a secreted group of vesicles, called "exosome” has been identified as major mediator of mesenchymal stem cells therapeutic efficacy. In this review, we will summarize the current literature on administration of exosomes released by mesenchymal stem cells in regenerative medicine and suggest how they could help to improve tissue regeneration following injury.